1988
DOI: 10.2307/1941646
|View full text |Cite
|
Sign up to set email alerts
|

Sun, Slope, and Butterflies: Topographic Determinants of Habitat Quality for Euphydryas Editha

Abstract: Thermal environments in a large, topographically diverse serpentine soil—based grassland were quantified and ranked using a computer model of clear sky insolation and shading on different slopes to determine the effects of microclimate on the rates of development of each of the life stages of the butterfly Euphydryas editha bayensis. Larvae developed to pupation earlier on warm slopes than on progressively cooler slopes. Availability of sunlight can be limiting for larvae, which bask indirect sun to raise body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
272
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(289 citation statements)
references
References 23 publications
12
272
1
2
Order By: Relevance
“…In fact, they did not. Weiss et al (1988) found that small differences in air temperatures in the field (68C on average between northand south-facing slopes) were enough to alter the relative timing of butterfly egg-laying and host-plant senescence, such that the window for feeding by prediapause larvae could be as long as 17 days (for north-facing slopes) or could collapse to nothing, with the average egg mass being laid after host senescence, on south-facing slopes. Singer (1971) found that the time difference between peak oviposition and 50 per cent host senescence was not constant among years, varying by 6 days across 4 years of study.…”
Section: Observed Responses Of Target Species To Climate Changementioning
confidence: 98%
See 1 more Smart Citation
“…In fact, they did not. Weiss et al (1988) found that small differences in air temperatures in the field (68C on average between northand south-facing slopes) were enough to alter the relative timing of butterfly egg-laying and host-plant senescence, such that the window for feeding by prediapause larvae could be as long as 17 days (for north-facing slopes) or could collapse to nothing, with the average egg mass being laid after host senescence, on south-facing slopes. Singer (1971) found that the time difference between peak oviposition and 50 per cent host senescence was not constant among years, varying by 6 days across 4 years of study.…”
Section: Observed Responses Of Target Species To Climate Changementioning
confidence: 98%
“…How much fecundity would she have gained by the same decision? We can make an educated guess by putting together the known mean weight of eggs (0.23 mg; Moore & Singer 1987) with the measured rates of weight gain by larvae in the field (Weiss et al 1988(Weiss et al , 1993. In late January, last instar larvae gained an average of 35 mg d 21 on a 158 south-facing slope and 8 mg d 21 on a 158 northfacing slope (Weiss et al 1993).…”
Section: Fecundity -Mortality Trade-offs As Drivers Of Asynchronymentioning
confidence: 99%
“…In the northern hemisphere, north facing slopes are typically cooler and wetter than south facing slopes, with significant differences in vegetation composition as a result. The distribution of larvae of the Bay checkerspot changes substantially from year to year across slopes, reflecting spatial patterns of prediapause survivorship (Weiss et al 1988). Larvae from egg masses laid on cooler slopes were found to nearly always have a better chance to reach diapause than those laid concurrently on warmer slopes, because of the later onset of plant senescence on cooler slopes.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of maintaining habitat on north facing exposures has been illustrated for the Bay checkerspot butterfly (Euphydryas editha bayensis), a threatened species also found in the San Francisco Bay area that utilizes grassland habitat (Weiss et al 1988). In the northern hemisphere, north facing slopes are typically cooler and wetter than south facing slopes, with significant differences in vegetation composition as a result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation